Funkcja krążków glinianych ludności kultury łużyckiej w świetle nowych znalezisk z Wielkopolski - Żychlińska, Justyna (Folia Praehistorica Posnaniensia, 2015)
Although the collection of “Lusatian” clay discs is quite significant, not much attention has been paid so far to their interpretation. The discs might have been used for various purposes in “Lusatian” society, e.g. as toys for children, or the Sun cult objects. They might have also played strictly utilitarian role of spindle whorls, polishing stones in pottery workshops, or miniature pads used in casting process. It would be difficult to accept any of the hypotheses exclusively, as it seems that the discs might have had various functions depending, among others, on the socio economic context in which they appeared.